The Properties of the Tide Current and Sediment at a Port of Southern China - Hongyan Shen; Ruicai Xie; Liqin Song (Advances in Materials Science and Engineering)
Environmental factors of projects in the sea area, such as tidal current characteristics and sediment transport patterns, play a decisive role in the safe operation of the harbor. Based on the observation data of tide level, tidal current, suspended sediment, and surface sediment in the Port of Shenquan, this paper focuses on the study of the characteristics of tidal current and sediment of projects in the sea area. According to the measured tide hydrograph, it can be concluded that the tide in the Port of Shenquan is irregular diurnal, and the flow of rising and falling tides is basically rectilinear. The velocity of the neap tide is higher than that of spring tide, which is mainly related to the strong winds and waves. The sand source is limited, and the sediment concentration in the water is very low. The hourly sediment concentration in each station fluctuates within a narrow range, independent of hourly velocity change. The sediment is coarse and fine, with a distribution pattern of coarse near shore, fine in deep water, coarse in East and West, and fine in the middle, and the sorting coefficient of sediment is medium to well.